Academic Community – the Target of the KGB of the Lithuanian SSR - Burinskaitė, Kristina (Genocidas ir rezistencija, 2014)
Starting from the very beginning of the Soviet occupation, the academic community became the target of the Soviet government. The government aimed to break the elite of society because of its potential and real resistance against the system and to subject it to its policies. Education and science institutions, therefore, were very important in the fight of the Soviet regime for human consciousness. Education was to be used for Communist indoctrination and instilling the values of the worldview important to the Soviet regime both in the country and outside the country. In addition, science institutions had an important role to play in the Cold War race with the West in the areas of science, technology and industry. With their discoveries, scientists had to help create the superiority of the Soviet system against the West. Furthermore, in the guise of scientific relations with the West, there was an opportunity for “intelligence activities”.The KGB, using its resources, helped the Communist Party implement its objectives in conjunction with the academic community. The KGB paid great attention to the behaviour of the representatives of the academic community, their attitudes towards government policies and other issues, monitored their relationships, analysed anti-Soviet manifestations among students and lecturers, and sought to identify and eliminate people who according to the authorities were unreliable. A network of agents was established for the implementation of these tasks, but it was not as broad as the KGB desired.Lithuanian scholars and scholars of the Lithuanian diaspora served both as the tool and the target of the implementation of the Communist Party propaganda campaigns. Achievements demonstrated by Lithuanian scientists in the West had to declare the progress of the Soviet system and also to discredit political campaigns by the diaspora. Scholars recruited by the KGB had a none-the-less important role to play in carrying out the KGB tasks of technical and industrial espionage in the West and thus helping create the image of superiority of the Soviet Union. Conferences and internships both in the West and in Lithuania were the perfect medium for collecting a variety of scientific and technical information. KGB agent reports show that achievements in medicine and in particular in the laser area, dominated in the records obtained by the agents.
Keywords: soviet regime; high education; antisoviet resistance; repressions